Family Perceptions of Palliative Care for Advanced-Stage Cancer Patients at Home - Mariam Dasat; Sigit Mulyono; Uswatul Khasanah; Stepanus Maman Hermawan (Jurnal Keperawatan Indonesia)
Family assistance with palliative care for advanced cancer patients is very important in optimizing patients’ quality of life. The purpose of this study was to explore family perceptions of palliative service provision to advanced cancer patients at home. The study adopted a qualitative research design with a phenomenological approach based on in-depth interviews with six participants. The main theme that emerged was family perceptions of participation in palliative care programs for cancer patients at home. There were three subthemes: family administering additional treatment, the patient being resigned to and accepting their condition, and the patient being helped by treatment. The families’ perceptions of caring for cancer patients at home were positive, and the patients demonstrated adaptive coping in dealing with their diseases. Family assistance to advanced cancer patients requires support from health workers as well as palliative cadres in the form of training on how to treat cancer patients and be good companions, as this can improve patients’ quality of life.